SIFAT OPTIK NANOMATERIAL ZnO DOPING NIOBIUM BERDASARKAN WAKTU SINTESIS - Iwantono Iwantono; Muhammad Pauji; Puji Nurrahmawati; Nashiha Chalvis Syahra (Universitas Riau, 2023)
This research was conducted to fabricate dye sensitized solar cell based on ZnO nanomaterial. Efforts to see the optical properties of niobium-doped ZnO are through UV-Vis characterization. Niobium-doped ZnO nanomaterials with growth time variations of 6, 8, and 10 hours have been successfully synthesized using hydrothermal methods. Samples resulting from synthesis were characterized using UV-Vis spectroscopy along with its energy gap. Samples with a synthesis time variation of 6 hours had higher absorbance absorption and a low energy gap of 3.09 eV.